Education in Europe : contemporary approaches across the continent - Feldges, Tom (The Routledge education studies series, 2023)
"This key text offers a detailed exploration of the wide range of theoretical approaches to theory, practice and research in Europe and how these can illuminate our understanding of contemporary education systems. Contributors working or living in countries across the continent offer their insight into different histories and contemporary problems, with each chapter exploring key themes and concepts to provoke critical thinking and discussion. Key areas and debates examined include: Educational poverty Perspectives on democracy and citizenship Theorising education and educational research Epistemic injustice in the curriculum Educational provision and ethos Drawing on these wide-ranging themes across a number of national contexts to provoke critical thinking and reflection, each chapter also includes discussion points and further reading. This book is most suitable for students working towards their BA or MA in Education Studies or other education related courses. It also offers a worthwhile resource for lectures and researchers engaged in the topic of international education"- Resumé vydavatel